Forestry research in Sub-Sahara Africa: time for reflection - Temu, A.B.; Kowero, G.S. (2000)
Despite the great social, economic and environmental diversity in countries of Africa South of Sahara (SSA), forestry research issues and advances are quite similar. This is partly influenced by historical facts relating to forest resource ownership and management. In most countries, governments own and manage forest resources. Forestry research institutes are in many countries tiny departments or units tucked under huge ministries or agricultural research organisations. Their visibility, much less their effectiveness, is barely significant, because they are poorly staffed and financed. The little available forestry research capacity is poorly managed. The few competent researchers are increasingly involved in administrative functions and looking for greener pastures. Economic policies imposed by global financial institutions constrain the recruitment of young scientists to undertake forestry research now and in the future. Although universities are much better resourced, their efforts are rarely linked with national research issues. They operate independently, far removed from real world issues. Through the intervention of some global stakeholders, some research institutes have developed their research agendas, but these have largely remained on the shelf for lack of implementation resources. Most ongoing work is donor-driven. There is a serious gap between forestry research and development. Research institutes do not have the capacity to extend their findings and are not properly linked with agricultural extension services or NGOs to get their messages to stakeholders, especially farmers. This delimits the usefulness of the little that could trickle from forestry research. This paper briefly discusses these issues and makes some recommendations. It is clear that SA countries and the global community have a role to play to redress the situation. SSA and the world stand to loose the opportunity to benefit from SSA forestry resources unless affirmative action is taken.